The Rise of White Collar Prophecy in Zimbabwe: A Psycho-Ethical Statement - Mangena, Fainos; Mhizha, Samson (Prophets, Profits, and the Bible in Zimbabwe: Festschrift for Aynos Masotcha Moyo, 2013)
In this chapter we interrogate the rising phenomenon of Pentecostal prophecy or what we call white collar prophecy as opposed to garmented prophecy or spirit-type church prophecy as described by Daneel. We begin this chapter by analysing the current circumstances in Zimbabwe which have given rise to Pentecostal or white collar prophecy which include poverty, disease and spirit possession among others. We also demonstrate how Pentecostal or white collar prophets tackle issues to do with health and well-being, wealth and prosperity, as well as spiritual growth and salvation. In discussing these pertinent issues in contemporary Zimbabwe, we draw our insights from Psychology and Ethics.
free